INTERNAL COMMUNICATION AND CORPORATE CULTURE: case study with a beverage company in the city of Taquaritinga-SP - de Oliveira, João Vitor; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2025)
Internal communication plays a fundamental role in the business sphere, not only due to the interaction between managers and employees, but by allowing members of the organization to feel welcomed and be able to participate more actively in processes and decision-making, thus contributing to success. of business. Therefore, this study explores concepts of organizational culture, focusing on how internal communication can be fundamental to the smooth running of business practices. After carrying out the theoretical contextualization, it presents a study with a beverage company in the city of Taquaritinga-SP, whose interviews with sector leaders allow for a deeper understanding of the importance of investing in internal communication. What can be seen, based on the close connection between theory and practice, is that investment in internal communication, combined with adequate training and modern resources for managers and employees, can contribute greatly to strengthening organizational culture and business success. These are, therefore, extremely important strategies that could not be left out of the business agenda.